Self-sustained rolling of a liquid crystal elastomer rod under inclined light illumination. (15th July 2022) - Su, Xiang; Li, Kai; Hu, Wenfeng; Xu, Peibao
Highlights: An inclined light is adopted to manipulate the rolling of a straight LCE rod. There exists an illumination angle range for triggering the self-sustained rolling. The straight rod can roll spontaneously from the rest under the inclined light. The rolling velocity can be controlled by the light intensity and illumination angle. Abstract: The self-sustained motion of active materials has the great application values in the fields of soft robots, medical devices, micro nano devices, etc., due to its advantage of directly harvesting energy from the environment. Recent experiment has discovered that a straight liquid crystal elastomer (LCE) rod on a horizontal surface can roll continuously under the vertical light illumination, but the start of rolling requires external disturbance. In this paper, we adopt an inclined light to manipulate the rolling of a straight LCE rod, and theoretically study its rolling behaviors to obtain the illumination angle range for triggering the self-sustained rolling. It is found that the rolling of straight LCE rod can be triggered from rest without external disturbance under the inclined light, which is different from the case of the vertical light illumination. In addition, the rolling velocity of the LCE rod can be easily controlled by the light intensity and illumination angle. These predictions are consistent with the existing experimental results. This study may guide the potential applications of the optically-responsive rod in soft robots, harvesting energy and active machinery. Graphical abstract: Image, graphical abstract